Trip report to Peru and Argentina - Debouck, Daniel G. (International Center for Tropical Agriculture, 1985)
As to prepare future germplasm explorations for Phaseolus in Peru and Argentina, a desk study was undertaken in the most important herbariums of Peru and Argentina. Plant identifications were made and data about phenology and distribution were recorded. Then a germplasm exploration was carried out in northwestern Argentina, mainly in Tucuman; 26 populations of Phaseolus vulgaris var aborigineus and 2 of Phaseolus augusti were described and sampled. Data on ecology, diseases and pests reactions of these populations are presented. Nodule samples were also collected.